Cocaine-induced leg ulceration. (30th August 2013) - Shawwa, Khaled; Alraiyes, Abdul Hamid; Eisa, Naseem; Alraies, M Chadi
Abstract : A 48-year-old woman presented with a red, pruritic and painful skin rash on her legs bilaterally after she snorted cocaine. This was associated with fever and cough. Physical examination showed large violaceous plaques and large flaccid bullae, involving bilateral lower extremities. Blood work showed neutropoenia with absolute neutrophil count of 0.64×10 9 cells/L. Antinuclear antibody, perinuclear antineutrophil cytoplasmic antibody and anti-double-stranded DNA were positive. Biopsy showed thrombogenic vasculopathy which is consistent mainly with levamisole ingestion that was reported with levamisole ingestion. The patient was counselled to stop cocaine misuse and treated with skin emollients and antibiotics for the pneumonia that was discovered on the chest X-ray. Skin ulcers improved and she was discharged in stable condition. Ten days after discharge, she was readmitted with new lesions and worsening necrotic ulcers from the old lesions. The patient admitted to snorting cocaine again a few days after being discharged.